Unique, non‐Earthlike, meteoritic ion behavior in upper atmosphere of Mars - J. M. Grebowsky; M. Benna; J. M. C. Plane; G. A. Collinson; P. R. Mahaffy; B. M. Jakosky (Geophysical Research Letters)
Abstract Interplanetary dust particles have long been expected to produce permanent ionospheric metal ion layers at Mars, as on Earth, but the two environments are so different that uncertainty existed as to whether terrestrial‐established understanding would apply to Mars. The Mars Atmosphere and Volatile EvolutioN (MAVEN) mission made the first in situ detection of the continuous presence of Na+, Mg+, and Fe+ at Mars and indeed revealed non‐Earthlike features/processes. There is no separation of the light Mg+ and the heavy Fe+ with increasing altitude as expected for gravity control. The metal ions are well‐mixed with the neutral atmosphere at altitudes where no mixing process is expected. Isolated metal ion layers mimicking Earth's sporadic E layers occur despite the lack of a strong magnetic field as required at Earth. Further, the metal ion distributions are coherent enough to always show atmospheric gravity wave signatures. All features and processes are unique to Mars.